Miksi liikuntatunneilla ei ole kiva käydä? : yläkoululaisten kokemuksia ja ajatuksia siitä, miksi koululiikunta ei kiinnosta - Paussu, Julia (2024)
The purpose of this study was to identify key factors related to the lack of enjoyment in physical education (PE) classes among students. The goals of this research were to clarify situations where negative perceptions toward PE classes were emerging and to find resolutions for increasing the level of enjoyment of PE classes. The research was qualitative. The research materials were gathered via an online questionnaire targeted towards 9th-grade students of a secondary school located in Uusimaa in February 2024. The final research material consisted of 11 questionnaire responses. The analysis method used was material-based content analysis, where the main operating model was thematization. The results of the study indicated that there are multiple factors related to the poor enjoyment of PE classes among students. The factors can be divided into factors related to the student and the group, the subject and the environment, and the teacher. Uncomfortable experiences emerged in situations where poor group spirit or bullying were present. The level of enjoyment in PE classes could be increased by boosting encouragement and making the environment more friendly. In addition, the teachers could increasingly involve the students in planning and implementing the classes, while introducing a variety of sports.